Investigation of integrated quality index of desserts and functional beverages - Свідло, Карина Володимирівна; Жулінська, Оксана Володимирівна (Technology audit and production reserves, 2015)
Implementation of the strategic directions of the development of food functional production in Ukraine is aimed at growth in production of healthy food. Among dietary factors relevant to maintaining health, working capacity and active longevity a decisive role belongs to the regular supply of the body’s functional complex of macro- and micronutrients contained in dietary supplements and physiologically active materials. Permanent deficit of such nutrients leads to the fact that the physical condition and overall health unstable, and this, in turn, contributes to the gradual development of chronic diseases, disorders of alimentary functions, including immune and specific resistance. The authors conducted a study that found that the adding of desserts and functional beverages, herbal dietary supplements and physiologically active materials in the food composition significantly improves organoleptic, physical and chemical and microbiological parameters of developed products. Calculations of integrated quality index for desserts and functional beverages and analogous product allow determining the overall impact of dietary supplements of plant origin and physiologically active materials on the quality formation in terms of figures. The possibility of directed regulation of competitiveness of products by determining the integrated quality index was determined.